Highly Sensitive, Rugged, and Wearable Fabric Strain Sensor Based on Graphene Clad Polyester Knitted Elastic Band for Human Motion Monitoring. Issue 16 (21st June 2019) - Reddy K, Ravinder; Gandla, Srinivas; Gupta, Dipti
Abstract: Smart electronic textiles are gaining a lot of importance in the field of flexible and wearable devices because of their lightweight, flexibility, deformability, and facile interaction with human skin. Herein, a simple, inexpensive, and scalable dip‐dry‐reduce approach method is reported to fabricate a flexible strain sensor using polyester knitted elastic band (PEB) as the platform material which is coated with reduced graphene oxide, and its potential applications are demonstrated in detecting both the subtle and large‐scale deformations of the human body. PEB is made by knitting polyester yarn around a series of inner rubber cores, which makes it very versatile, lightweight, and shrink and wear resistant. The strain sensor can detect the small strains down to 0.2% with high sensitivity/gauge factor (GF) of 30 within in a strain range of 0–1%, and also shows excellent performance in terms of sensitivity (GF of 34 and 5 within in a strain range of 0–20%, 20–50%, respectively), negligible drift, stability, and durability over 6000 cycles. Moreover, the strain sensor can sense and record large‐scale human body motion even under water‐immersed condition and also exhibits negative temperature coefficient effect with a temperature coefficient of resistance of 0.677%°C −1 . Abstract : The reduced graphene oxide clad polyester knitted elastic band sensor exhibits high gauge factor of 30 and 34 within the small and large strain range, respectively and detects tiny strains down to 0.2%. The proposed sensor shows excellent performance in terms of negligible drift, stability, durability, and repeatability and detects a range of human motions even under water‐immersed condition with excellent stability and reliability.